Development of quorum-sensing-based genetic circuits that enable programmable functionalities in escherichia coli - Tan, Mui Hua (2014)
Pseudomonas aeruginosa is a prevalent nosocomial pathogen which is a major cause of urinary tract disease and hospital secondary infections. With the emergence of antibiotic resistant bacteria, the number of methods to eradicate P. aeruginosa has become more limited. This is especially true when P. aeruginosa is in the biofilm state. The biofilm is the form whereby the cells are encompassed by a matrix comprising of exopolysaccharides, DNA and proteins. Because of the antibiotic-resistance property conferred by the matrix, the biofilm usually leads to chronic infections and is very difficult to treat. P. aeruginosa biofilm formation is regulated by quorum sensing. Quorum sensing regulates gene expression in response to changes in population density of bacteria. Bacteria communicate by releasing and detecting the intercellular signalling molecules called autoinducers. As the population density increases, the concentration of autoinducers increases correspondingly. Once the threshold concentration of autoinducers is reached, a density-dependent change in gene expression is triggered, which eventually regulates physiological activities such as virulence, symbiosis, motility and biofilm formation. P. aeruginosa produces the autoinducer N-acyl homoserine lactone (AHL) as their primary specific signalling molecule for quorum-sensing. With its high specificity, the quorum sensing mechanism of P. aeruginosa can be exploited for the targeted and inducible regulation of desirable proteins to perform specific useful functions. The work described in this thesis aimed to develop P. aeruginosa quorum-sensing-based genetic circuits that would enable clinically relevant programmable functionalities in Escherichia coli: protein release, directed motility, and pathogen killing. Toward this aim, I have developed three systems with a quorum sensing device as a control system: (1) a P. aeruginosa quorum sensing-based genetic circuit that enabled cell density-dependent autoregulatory lysis for the release of macromolecules, (2) a probiotic strain with integrated P. aeruginosa quorum sensing device for specific sensing of P. aeruginosa and eventually killing of clinical isolates of P. aeruginosa, and (3) a genetic circuit that enables engineered E. coli to move distinctly towards P. aeruginosa and kill the human pathogen.